Choosing the optimal dose in sublingual immunotherapy: Rationale for the 300 index of reactivity dose. Issue 1 (December 2015) - Demoly, Pascal; Passalacqua, Gianni; Calderon, Moises; Yalaoui, Tarik
Abstract Sublingual immunotherapy (SLIT) is an effective and well-tolerated method of treating allergic respiratory diseases associated with seasonal and perennial allergens. In contrast to the subcutaneous route, SLIT requires a much greater amount of antigen to achieve a clinical effect. Many studies have shown that SLIT involves a dose–response relationship, and therefore it is important to use a proven clinically effective dose from the onset of treatment, because low doses are ineffective and very high doses may increase the risk of side effects. A well-defined standardization of allergen content is also crucial to ensure consistent quality, potency and appropriate immunomodulatory action of the SLIT product. Several methods of measuring antigenicity are used by manufacturers of SLIT products, including the index of reactivity (IR), standardized quality tablet unit, and bioequivalent allergy unit. A large body of evidence has established the 300 IR dose of SLIT as offering optimal efficacy and tolerability for allergic rhinitis due to grass and birch pollen and HDM, and HDM-induced moderate, persistent allergic asthma. The 300 IR dose also offers consistency of dosing across a variety of different allergens, and is associated with higher rates of adherence and patient satisfaction. Studies in patients with grass pollen allergies showed that the 300 IR dose has a rapid onset of action, is effective in both adults and children in the short term and, when administered pre-coseasonally in the long term, and maintains the clinical benefit, even after cessation of treatment. In patients with HDM-associated AR and/or asthma, the 300 IR dose also demonstrated significant improvements in symptoms and quality of life, and significantly decreased use of symptomatic medication. The 300 IR dose is well tolerated, with adverse events generally being of mild or moderate severity, declining in frequency and severity over time and in the subsequent courses. We discuss herein the most important factors that affect the selection of the optimal dose of SLIT with natural allergens, and review the rationale and evidence supporting the use of the 300 IR dose.